ATTITUDES OF FUTURE PEDAGOGUES TO OPTION OF UTILISING PROJECT METHOD IN AMBIENT OF NURSERY SCHOOL - BLAZKOVA, Hana (Trends in education, 2010)
The article analyze knowledge of student group studying field of study Pedagogy for nursery schools PdF UP Olomouc in a section of project method, their opinion to possibility of utilising this effective method in ambient of nursery school during development of working skills.
Keywords: research; respondent; project method; frequency of utilising project method.